The Measurement of Efficiency and Productivity of Small Banks Comparative Study in Central Java and Yogyakarta - Evania Herindar; Ikha Nur Syamsiyah (Journal of Business Management and Islamic Banking, 2023)
Research Aims: The purpose of this study was to determine the effect of promotion and service quality on students' interest in choosing SIPINTAR products at PT. Bank Perkreditan Rakyat Pembangunan Kerinci. Methodology: This study uses a quantitative research design with a survey approach. The research sample was 60 students in Kerinci Regency while the sampling technique was the convenience sampling method. The data analysis technique used multiple linear analysis, while the hypothesis testing used the statistical t test and F test with the help of the IBM SPSS 26 application. Research Findings: The results of this study found that partially promotion had a positive and significant effect on students' interest in using SIPINTAR products, while service quality had no effect on students' interest in using SIPINTAR PT. Kerinci Development People's Credit Bank. The results of the F test show that promotion and service quality simultaneously have a significant effect on using PT. SIPINTAR products. Kerinci Development People's Credit Bank, with the magnitude of this influence, namely 20.6%. Theoretical Contribution: This research is beneficial for the development of the banking business, especially for regional banks. Research limitation and implication: This study has limitations, namely only examining promotion factors and service quality in influencing the intention to save. However, the results of this study provide information that promotion is a factor in forming interest in using banking products.